The role of exercise-and high fat diet-induced bone marrow extracellular vesicles in stress hematopoiesis - Vanhie, James J.; Kim, Wooseok; Ek Orloff, Lisa; Ngu, Matthew; Collao, Nicolas; De Lisio, Michael (Frontiers in Physiology, 2022)
Exercise and obesity regulate hematopoiesis, in part through alterations in cellular and soluble components of the bone marrow niche. Extracellular vesicles (EVs) are components of the bone marrow niche that regulate hematopoiesis; however, the role of exercise training or obesity induced EVs in regulating hematopoiesis remains unknown. To address this gap, donor EVs were isolated from control diet-fed, sedentary mice (CON-SED), control diet-fed exercise trained mice (CON-EX), high fat diet-fed, sedentary mice (HFD-SED), and high fat diet-fed, exercise trained mice (HFD-EX) and injected into recipient mice undergoing stress hematopoiesis. Hematopoietic and niche cell populations were quantified, and EV miRNA cargo was evaluated. EV content did not differ between the four groups. Mice receiving HFD-EX EVs had fewer hematopoietic stem cells (HSCs) (p<0.01), long-term HSC (p<0.05), multipotent progenitors (p<0.01), common myeloid progenitors (p<0.01), common lymphoid progenitors (p<0.01), and granulocyte-macrophage progenitors (p<0.05), compared to mice receiving HFD-SED EVs. Similarly, mice receiving EX EVs had fewer osteoprogenitor cells compared to SED (p<0.05) but enhanced mesenchymal stromal cell (MSC) osteogenic differentiation in vitro (p<0.05) compared to SED EVs. HFD EVs enhanced mesenchymal stromal cell (MSC) adipogenesis in vitro (p<0.01) compared to CON EVs. HFD-EX EVs had lower microRNA-193 and microRNA-331-5p content, microRNAs implicated in inhibiting osteogenesis and leukemic cell expansion respectively, compared to HFD-SED EVs. The results identify alterations in EV cargo as a novel mechanism by which exercise training alters stress hematopoiesis and the bone marrow niche.